Are wars detrimental to the environment? Evidence from air pollution and land use - Marrouch, Walid (2024)
This paper studies the long-run effect of war on environmental quality. Using data from the UCDP/PRIO Armed Conflict Dataset and the World Development Indicators, we apply a generalized difference-in-differences methodology. We compare the airborne emissions of countries that have experienced war after World War II (WWII) before and after the occurrence of the war event with the emissions of countries that did not experience any war after WWII. We find that, although wars decrease per capita CO2 emissions, they increase CO2 intensity. We also examine the effect of war on forest cover, which is found to be positive across all specifications. Lastly, we document differential effects by war type, country’s legal origins, and income level.